Putative anti-proliferative effect of Indian mustard (Brassica juncea) seed and its nano-formulation - Virk Promy; Awad Manal A.; Alanazi Meznah M.; Hendi Awatif A.; Elobeid Mai; Ortashi Khalid M.; Alrowaily Albandari W.; Bahlool Taghreed; Aouaini Fatma (Green Processing and Synthesis, 2023)
Over the past few decades, nanotechnology has shown promising prospects in biomedicine and has a proven impact on enhancing therapeutics by facilitating drug delivery. The present study brings an amalgamation of nanoscience and “clean technology” by fabricating nature-friendly nanoparticles (NPs) sans the use of chemical surfactants using Indian mustard seed, Brassica juncea L. The as-synthesized NPs were characterized to assess their average size, crystallinity, morphology, and constituent functional groups through conventional techniques: dynamic light scattering (DLS), X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR). The NPs were crystalline in nature and exhibited a mean size of 205.5 nm (PDI of 0.437) being primarily polygonal in shape. Additionally, the therapeutic efficacy of the green NPs was evaluated based on their cytotoxic effect against two human cancer lines, MCF-7 and HepG-2. Both the NPs and the bulk seeds showed a dose-dependent cytotoxic effect. However, an assessment of the antiproliferative/cytotoxic potential of the green NPs versus the bulk seeds showed that the NPs were relatively more efficacious on both cell lines. Taken together, the mustard seed NPs could be potential nutraceuticals considering the green credential in their mode of biosynthesis.